An Excellent Scribe and Servant of the Great Goddess: The Textual Development and Interpretation of Coffin Text 533 - Furutani, Jordan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
CT 533, one of the divine scribe spells among the Coffin Texts, is an important early example of the interaction of Thoth and Hathor. The spell’s text, textual history, and theology are extensively discussed in order to expose the early form of the Myth of Distant Goddess as well as early concepts of Thoth’s role in her pacification. The spell’s earliest versions primarily dealt with Thoth as advocate for the deceased, in its later manifestations the spell uses Hathoric material related to the Myth of the Distant Goddess to reinforce these themes. This development is connected to the cult-center at Cusae.